Supporting IDP resistance strategies - Poe Shan K Phan; Stephen Hull (Forced Migration Review, 2008)
Whether in hiding or living under military control, displacedvillagers of Karen State and other areas of rural Burmahave shown themselves to be innovative and courageousin responding to and resisting military abuse. Theyurgently need increased assistance but it is they whoshould determine the direction of any such intervention.